2017
DOI: 10.1002/ijgo.12074
|View full text |Cite
|
Sign up to set email alerts
|

A review of the preventability of maternal mortality in one hospital system in Louisiana, USA

Abstract: The factors most predictive of mortality were late entry to prenatal care, critical status requiring transfer from an outside facility, and non-private insurance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
0
0
1
Order By: Relevance
“…Nachfolgend wurden in einigen Staaten der USA wie in Kalifornien [48], in Illinois [49] und in Louisiana [50] weitere Analysen zur Vermeidbarkeit von Müttersterbefällen (bis 1 Jahr nach der Geburt) durchgeführt (vgl. ▶Tab.…”
Section: Landunclassified
“…Nachfolgend wurden in einigen Staaten der USA wie in Kalifornien [48], in Illinois [49] und in Louisiana [50] weitere Analysen zur Vermeidbarkeit von Müttersterbefällen (bis 1 Jahr nach der Geburt) durchgeführt (vgl. ▶Tab.…”
Section: Landunclassified
“…Early and comprehensive prenatal care is crucial in the United States to minim-ize the likelihood of negative outcomes for both the mother and the baby (Morong, Martin, Ware, & Robichaux, 2017;Waits, Smith, & Hurst, 2020;Wallace, Dyer, Felker-Kantor, Benno, Vilda, Harville, & Theall (2021). Studies have shown a significant number of pregnancy complications in the country, with a majority of women experiencing at least one complication (Law, McCoy, Lynen, Curkendall, Gatwood, Juneau, & Landsman-Blumberg (2015).…”
Section: Introductionmentioning
confidence: 99%